Co-carriage of Staphylococcus aureus and Streptococcus pneumoniae among children younger than 2 years of age in a rural population in Pakistan - Shahira Shahid; Muhammad Imran Nisar; Fyezah Jehan; Sheraz Ahmed; Furqan Kabir; Aneeta Hotwani; Sahrish Muneer; Muhammad Farrukh Qazi; Sajid Muhammad; Asad Ali; Anita K.M. Zaidi; Najeeha T. Iqbal (Elsevier, 2023)
Objectives: Staphylococcus aureus and Streptococcus pneumoniae are common colonizers of the human nasopharynx. In this study, we describe S. aureus nasopharyngeal carriage and evaluate its association with S. pneumoniae carriage post-10-valent pneumococcal conjugate vaccine (PCV10) introduction in Pakistan. Methods: A serial cross-sectional study was undertaken from 2014 to 2018, children <2 years were randomly selected, and nasopharyngeal swabs were collected using standard WHO guidelines. S. aureus and S. pneumoniae isolates were identified using standard methods and tested for antimicrobial susceptibility by the standard Kirby-Bauer disk-diffusion method as per Clinical & Laboratory Standards Institute (CLSI) recommendations. Regression analysis was used to determine predictors associated with S. aureus carriage. Results: We enrolled 3140 children. S. aureus carriage prevalence was 5.6% (176/3140), and 50.1% (81/176) of the isolates were methicillin-resistant S. aureus (MRSA). S. aureus carriage was higher in the absence of pneumococcus compared to isolates in which pneumococcus was present (7.5% vs 5.0%). S. aureus carriage was negatively associated with pneumococcal carriage, being in 3rd and 4th year of enrollment, and vaccination with two and three PCV10 doses, in addition, fast breathing, ≥2 outpatients visits, and rainy season were positively associated. The following resistance rates were observed: 98.9% for penicillin, 74.4% for fusidic acid, and 23.3% for gentamicin, 10.2% for erythromycin, and 8.5% for cotrimoxazole. All isolates were susceptible to amikacin. Conclusions: Overall S. aureus carriage prevalence was low, PCV10 vaccine was protective against the carriage. The proportion of MRSA carriage and antimicrobial resistance was high in this community warranting continuous monitoring for invasive infections.